2022
DOI: 10.3390/jmse10081039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propeller Cup on the Reduction of Fuel Consumption in Realistic Weather Conditions

Abstract: This paper presents the effect of a propeller cup on the propeller cavitation and the fuel consumption of a bulk carrier in both calm water and different weather conditions towards improving the energy efficiency of the ship and reducing the level of emissions in terms of design and operation. Based on the propeller optimization model, previously developed that couples NavCad and a Matlab code to select the geometry and the operating point of the propeller at the engine operating point with minimum fuel consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Finally, the socalled "overall resistance index" accounting for both ice and hydrodynamic resistance was estimated, which permitted the selection of a single optimal configuration. Tadros et al [5] studied some of the special aspects of the optimum propeller design. In particular, the effect of cupping the propeller blades was investigated.…”
Section: Contributions' Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the socalled "overall resistance index" accounting for both ice and hydrodynamic resistance was estimated, which permitted the selection of a single optimal configuration. Tadros et al [5] studied some of the special aspects of the optimum propeller design. In particular, the effect of cupping the propeller blades was investigated.…”
Section: Contributions' Overviewmentioning
confidence: 99%
“…In paper [6], Tadros et al explored a more traditional method of improving propulsive efficiency, presuming the application of contra-rotating propellers possibly also combined with cupping. The numerical study was based on the same methodology and software as used in [5], but only the calm-water condition was considered. The effectiveness of the contra-rotating propellers was confirmed, and it was demonstrated that cupping further boosts the propulsive efficiency.…”
Section: Contributions' Overviewmentioning
confidence: 99%
“…This can help to select an optimum propeller based on the system configurations to operate at the engine operating point with minimum fuel consumption, which can help to reduce the amount of fuel consumed along the ship trip with different weather conditions while complying with the cavitation, strength and noise issues (Tadros et al, 2021a;Ghaemi and Zeraatgar, 2021;Tavakoli et al, 2021;Tadros et al, 2022e;Tadros et al, 2022b;Tadros et al, 2023b). The use of empirical formulas shows its effectiveness in reaching the optimal solution in a few minutes with high accuracy.…”
Section: Energy Efficiency Design Indexmentioning
confidence: 99%
“…The final category to be considered is the ship operation Vettor et al, 2018;Tadros et al, 2022e;Zaccone et al, 2018), where the path of the ship can be optimized based on the opinion of the ship master to use the less amount of fuel, ensure the safety of the ship in high weather conditions and reach the destination at the required time. These models require a combination of several types of data in terms of fuel consumption as approved by MEPC 79 and different types of computational models in addition to the multi-objective optimization technique to achieve optimal solutions intelligently.…”
Section: Energy Efficiency Design Indexmentioning
confidence: 99%
“…In the second solution group, the investigation on cavitation reduction of the propeller with blade cup by CFD method conducted by Tadros et al [6] demonstrated that increasing the percentage of cupping reduces the propeller cavitation and saving about 5% -7% of the fuel consumption. Mizzi et al [7] researched design optimization of propeller boss cap fins by numerical simulation, improving propeller performance by 1.3%.…”
Section: Introductionmentioning
confidence: 99%